Unveiling the three-dimensional melting fraction of Si-C nano-enhanced paraffin wax PCM in Li-ion battery pack cooling plates - Afzal, Asif; Buradi, Abdulrajak; Agbulut, Umit; Bakir, Huseyin; Alwetaishi, Mamdooh; Hussain, Fayaz; El-Shafay, A. S.; Park, Sung Goon (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
Adding a measured quantity of nanoparticles in phase change material for effective and efficient thermal management of lithium-ion battery packs is an extensively reported passive cooling method. The numerical simulation of SiC(Silicon Carbide) nano-embedded paraffin wax enclosed in a serpentine-shaped rectangular plate (95 mm x 65 mm x 3 mm) is examined in this paper. Five battery cells are placed on each side of the plate, and three different temperatures, 60 degrees C, 65 degrees C, and 70 degrees C of battery cells are used in the present investigation. The depth of contact between the plate and battery cell is kept constant at 0.5 mm, with the assumption of perfect thermal interaction. The CFD (Computational Fluid Dynamics) simulation makes use of a finite volume scheme to solve the second-order mass, momentum, and energy conservation equations. The mushy zone value at the solid-liquid interface is kept constant at 104, while the velocity-pressure correction is performed using the PISO (Pressure-Implicit with Splitting of Operators) algorithm. The time-dependent temperature, melting fraction, velocity vectors, and temperature gradients are plotted. The results show that using Si-C nanoparticles enhances heat transfer by maintaining a uniform temperature distribution within the PCM (Phase Change Material). It takes approximately 20 s for convection mode to initiate, while the latent heat of absorption of PCM increases with the increase in battery cell temperature. The average rate at which the melting percentage and temperature of nano Si-C PCM increase per second is 0.45%, 0.5%, 0.55%, and 0.025 degrees C, 0.05 degrees C, 0.07 degrees C respectively, for battery cell temperatures of 60 degrees C, 65 degrees C, and 70 degrees C.
Keywords: Si - C nanoparticles; Paraffin wax; PCM; Li-ion battery; Cooling plate; PHASE-CHANGE MATERIALS; THERMAL MANAGEMENT-SYSTEM; PERFORMANCE; Thermodynamics; Mechanics